Importance of providing elemental landscape in Darulaman lake recreation area, Jitra, Kedah - Shareh Musa, Sharifah Meryam; Senapi, Nurhafezawani; Shafii, Haryati; Md Yassin, Azlina; Zainal, Rozlin (Universiti Pendidikan Sultan Idris, 2018)
Landscape construction at the recreational park is one of the facilities that the Local Authority (PBT) has to provide for the community in a city. Construction of recreational park landscapes in the country still does not reach the level of satisfaction desired by consumers and visitors. Therefore, this study was conducted to study the landscape construction, referring to the case studies at Darulaman Lake Recreational Park, Jitra. The objective of this study is to identify the importance of landscape building to consumers, and to study consumer perceptions on the construction of landscapes in Darulaman Lake Recreational Park. The methodology used in the study were interviews and questionnaires. This study involved 80 respondents from users who visited Darulaman Lake and interviewed with the management of Darulaman Lake (BDB Land Sdn Bhd). The findings show that respondents agree with the construction of landscapes in recreational parks as it brings importance to consumers and consumer perceptions of Darulaman Lake Recreational Park in terms of management and preparation of landscape elements.